Case Study of Paranoid Schizophrenia in Young Adults - Putra, Hamzah; Desy Anggraeni (Scientia Psychiatrica, 2024)
Introduction: An individual with paranoid schizophrenia exhibits a preoccupation with one or more delusions and experiences frequent auditory hallucinations. This study aimed to describe the diagnosis and treatment of paranoid schizophrenia in young men. Case presentation: A 20-year-old man was found sitting in the middle of traffic on a bustling route, prompting the cops to transport him to the emergency department for medical care. The patient showed poor personal hygiene during the mental health assessment, appearing dirty and untidy. He constantly paces the examining room, ensuring his back is always against the wall. He exudes a subtle sense of unease with his environment. He characterizes his demeanor as "adequate." Despite his lack of emotional expression, his emotional expression remains constant. The working diagnosis for this patient was paranoid schizophrenia. The patient was prescribed a regimen of atypical antipsychotic medication, specifically risperidone, at a dosage of 2 mg, to be taken twice daily. The treatment will continue for 6 months, with monthly assessments of the patient's symptoms to gauge the medication's effectiveness. Conclusion: Prior to making a diagnosis of schizophrenia, it is critical to rule out any potential etiologies for the manifestation of psychotic symptoms, such as substance abuse, medication use, or medical conditions. In contrast to prior "typical" antipsychotics such as chlorpromazine and haloperidol, atypical antipsychotics provide a multitude of advantages. Although conventional medications are efficacious in treating the positive symptoms of schizophrenia, they may inadvertently worsen or even induce the negative symptoms.